2018
DOI: 10.11159/iccpe18.108
|View full text |Cite
|
Sign up to set email alerts
|

Torrefaction of Barley Straw for the Co-Production of Energy and Adsorbent Materials

Abstract: The purpose of this study was first to examine and then to maximize, the adsorbency of torrefied barley straw, in order to remove basic dyes like Methylene Blue (MB) from wastewater. On the other hand, the effect of the torrefaction process on the heating value of the material was investigated. Moderate modification conditions (220 ºC, 20 min) were found to maximize adsorbency of modified barley straw. The experimental data were simulated by a pseudo-second order kinetic model. The torrefaction also significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The high heating values of raw and torrefied biomasses at varied torrefaction operating conditions are presented in Table 1. In case of raw biomass, the HHV of wood waste i.e., 19.91 MJ•kg −1 was slightly higher than those of agricultural wastes i.e., 18.83 MJ•kg −1 for BS and 18.12 MJ•kg −1 for CS. As expected, the HHV of the torrefied biomass increased with increasing torrefaction temperature.…”
Section: Influence Of Torrefaction On the Energy Content Of Biomass (...mentioning
confidence: 83%
See 2 more Smart Citations
“…The high heating values of raw and torrefied biomasses at varied torrefaction operating conditions are presented in Table 1. In case of raw biomass, the HHV of wood waste i.e., 19.91 MJ•kg −1 was slightly higher than those of agricultural wastes i.e., 18.83 MJ•kg −1 for BS and 18.12 MJ•kg −1 for CS. As expected, the HHV of the torrefied biomass increased with increasing torrefaction temperature.…”
Section: Influence Of Torrefaction On the Energy Content Of Biomass (...mentioning
confidence: 83%
“…Torrefied biomass can also be used as a feedstock in the pyrolysis [16] and gasification [17] processes. Additionally, torrefied biomass also can be used as adsorbent [18][19][20][21] and for soil amendment [22,23]. The yield of torrefied biomass depends on the operating temperature and residence time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercially, the torrefaction process is a potential scenario to be applied in various applications. Salapa et al revealed the high adsorption capacity of torrefied barley straw of 11.65 mg/g at operating parameters of 220 °C and 20 min (Salapa et al 2018). Other researchers evaluated the torrefaction process's impacts at different contact periods (i.e.…”
Section: Torrefactionmentioning
confidence: 99%